Late reopening of an occluded infarct related artery improves left ventricular function and long term clinical outcome. Issue 5 (14th April 2005) - Piscione, F; Galasso, G; De Luca, G; Marrazzo, G; Sarno, G; Viola, O; Accardo, D; Chiariello, M
Abstract : Objective: To assess effects on left ventricular (LV) function and on long term clinical outcome of late percutaneous transluminal coronary angioplasty (PTCA) of a chronically occluded infarct related artery. Methods: 65 patients who underwent PTCA a mean (SD) of 6.0 (1.2) months after a previous myocardial infarction were divided in two groups according to dilated artery patency status after PTCA: group 1 (35 patients with TIMI (thrombolysis in myocardial infarction) grade 3 flow) and group 2 (30 patients with TIMI grade 0–2 flow). Echocardiography was performed at admission and at six months' follow up. A three year follow up was conducted with major adverse cardiac events (MACE) as end points. Results: At follow up, group 1 had improved global LV ejection fraction (48.7% v 43.6%, p < 0.001) and LV indexed end diastolic and end systolic volumes (75 v 86 ml/m 2 and 40 v 53 ml/m 2, respectively, p  =  0.011) compared with group 2. Kaplan-Meier analysis showed a higher incidence of cardiac death (p  =  0.02) and MACE (p < 0.0001) in group 2. TIMI 3 after PTCA was an independent predictor of event-free survival at follow up. Conclusion: Late PTCA of a chronically occluded infarct related artery improves LV function, reduces cardiac death, and improves long term clinical outcome.